A281 RISK FACTORS ASSOCIATED WITH PROGRESSION OF BARRETT'S ESOPHAGUS, LOW GRADE DYSPLASIA & HIGH GRADE DYSPLASIA TO ESOPHAGEAL ADENOCARCINOMA. (15th March 2019) - Chahal, D; Pi, S; Duggan, S; Donnellan, F; Enns, R A
Abstract: Background: Barrett's Esophagus (BE) is a known risk factor for development of Low Grade Dysplasia (LGD), High Grade Dysplasia (HGD) and ultimately Esophageal Adenocarcinoma (EAC). Only a small minority of patients with BE progress to LGD, HGD or EAC and it remains difficult to predict those at higher risk. As such, current screening methods for BE have resulted in only modest mortality benefit and are not thought to be cost-effective. Aims: The purpose of this study was to investigate characteristics of patients with BE at St. Paul's Hospital, in order to help predict those who may be at higher risk of progression to EAC. Methods: A retrospective chart review of all LGD, HGD and EAC diagnosed at St. Paul's Hospital from 2012–2016 was conducted. The list of all patients LGD, HGD and EAC was obtained through St. Paul's Hospital Department of Pathology after ethics approval. Results: 132 patients met inclusion criteria. There 47 (35.6%) patients with no dysplasia, 29 (22.0%) with LGD, 35 (26.5%) with HGD and 21 (15.9%) with EAC as their highest risk pathology. There were 24 (18.2%) female patients and 108 (81.8%) male. Compared with non-EAC (No dysplasia, LGD or HGD), patients with EAC had higher rate of smoking history (52.4% vs. 20.7%, p=0.002), higher rate of prior malignancy of any type (33.3% vs. 8.1 %, p=0.001), older mean age at time of BE diagnosis (71.0 +/- 8.3 vs. 61.3 +/- 12.2, p=0.001), and greater rate of mucosal irregularity (nodularity, ulceration, structuring) at time of endoscopy (85.7% vs. 28.8%, p<0.001). Patients with EAC also had greater incidence of family history of breast cancer (22.2% vs. 6.2%, p=0.027) and lung cancer (23.5% vs. 4.1%, p=0.004) compared to those without EAC. Patients with and without EAC did not differ in terms of alcohol use (71.4% vs. 70.3%), p=0.915), reflux symptoms (85.7% vs. 91.9%, p=0.367), presence of esophagitis (LA grade) (4.8% vs. 7.2%, p=0.684), presence of hiatal hernia (85.0% vs. 83.8%, p=0.891), or family history of esophageal cancer (11.8% vs. 13.4%, p=0.854). Conclusions: Patients with BE who developed EAC had higher incidence of smoking, prior malignancy, family history of lung or breast CA, and mucosal irregularity as well as older age at diagnosis of BE compared to those who did not develop EAC. They did not differ in incidence of alcohol use, reflux symptoms, esophagitis, hiatal hernia or family history of esophageal cancer. Identifying Barrett's patients who are at higher risk of developing EAC remains difficult and recent data suggest that mass screening and surveillance protocols have had limited impact on mortality. Our data provides clarity about risk factors that may aid in determining which patients would benefit from earlier screening or increased frequency of surveillance. Funding Agencies: None